Factors Influencing Women's Advancement in Leadership Positions in The Czech Republic - Kostúrová, Michaela (2025)
This thesis explores the persistent gender gap in leadership within the Czech Republic, focusing on the organisational and personal factors that influence women’s career progression. The theoretical section presents an overview of leadership, organisational culture, and inclusion through a gendered lens, identifying long-standing biases in leadership archetypes and workplace dynamics. It focuses on analysing factors and policies promoting women in leadership and introduces the current situation of female leadership in the Czech Republic. The research applies a qualitative methodology based on semi-structured interviews with fifteen female leaders across sectors in the Czech Republic. Through deductive coding it discovers and identifies what factors influence women’s advancement to leadership positions in Czech Republic. The findings are based on lived experiences that reveal both enabling support systems and ongoing barriers, such as perceptions of masculine leadership norms or challenges of work-life balance. The thesis determines organisational support and short maternity leave as most important factors for women, and detects gaps in these factors, where there is a place for improvement. Based on these insights, the thesis presents strategic recommendations for companies to advance more of their women employees to leadership positions and offers advice for individual women navigating their own leadership journeys.